Gene expression profile analysis of gallic acid-induced cell death process - Ho Man Tang (Nature Portfolio, 2021)
Abstract Gallic acid is a natural phenolic compound that displays anti-cancer properties in clinically relevant cell culture and rodent models. To date, the molecular mechanism governing the gallic acid-induced cancer cell death process is largely unclear, thus hindering development of novel therapeutics. Therefore, we performed time-course RNA-sequencing to reveal the gene expression profiles at the early (2nd hour), middle (4th and 6th hour), and late (9th hour) stages of the gallic acid-induced cell death process in HeLa cells. By Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, we found significant changes in transcription of the genes in different types of cell death pathways. This involved the ferroptotic cell death pathway at the early stage, apoptotic pathway at the middle stage, and necroptotic pathway at the late stage. Metabolic pathways were identified at all the stages, indicating that this is an active cell death process. Interestingly, the initiation and execution of gallic acid-induced cell death were mediated by multiple biological processes, including iron and amino acid metabolism, and the biosynthesis of glutathione, as targeting on these pathways suppressed cell death. In summary, our work provides a dataset with differentially expressed genes across different stages of cell death process during the gallic acid induction, which is important for further study on the control of this cell death mechanism.